AUGMENTED REALITY GROUND MARSHALL AIRPLANE BERBASIS ANDROID - Remawati, Dwi; Prabowo, Iwan Ady; Wahyuno, Tulus (Jurnal Teknologi Informasi dan Komunikasi (TIKomSiN), 2020)
Â Many people do not know the figure of a ground marshall, the task is simple but very important, so that it becomes an interesting student learning material that is how a ground marshall can park a plane requires more interactive and communicative teaching and learning facilities, so students can more easily understand the material. Augmented Reality is one of the innovative and creative new learning methods because it uses technology that can provide visualization to Marshalling Signals that are not well-known by users, so application users will get information while developing user imagination.Â the results with the questionnaire from respondents, after testing the application, the application is the best application according from respondents with an average value 92.7% while the first application is only 88.6%. Â Keyword : Ground Marshall, Augmented reality, Marshalling Signals